HISTORICAL-ADVENTUROUS NARRATIVE «REID U NEVIDOME» BY YURII TYS: THE ORIGINALITY OF EPIC THINKING - Залевська, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
On the material of Yurii Tys’s narrative (povist) «Reid u nevidome» the article analyses the peculiarities of the writer’s fictional thinking, researches the inner and outer structure of the work, as well as its system of images.